Formation age of Jiudong Sandy Land, in the western Hexi Corridor, NW China. (20th April 2019) - Chen, Dianbao; Pan, Baotian; Hu, Xiaofei; Wang, Ying; Pan, Xumin; Wang, Wei; Zhang, Jian; Pang, Hongli
Abstract: Jiudong Sandy Land in the western Hexi Corridor is one of the dust source regions of the Chinese Loess Plateau and is highly sensitive to climate change. Determination of when this sandy land formed would help resolve major questions about the desertification history of inland Asia; however, until now, this has been hindered by the lack of depositional records. Here, we report the results of optically stimulated luminescence (OSL) dating, grain size and grain surface analyses from a new drill core obtained from Jiudong Sandy Land. Our aims are to constrain its age of formation. Analysis of sedimentary facies reveals that the sediments in the lower part of the core (35.2–16.7 m) were deposited by fluvial processes, but that the sediments in the upper part consist primarily of aeolian sand. The OSL dating results indicate that the transition from fluvial to aeolian facies occurred at ∼89.8 ± 7.6 ka. Combined with various loess-based environmental proxies from Jiudong Basin, the new litho- and chronostratigraphic evidence reported in this study indicates that the age of ∼89.8 ± 7.6 ka represents the formation age of the Jiudong Sandy Land.